PENERAPAN PENDEKATAN KONTEKSTUAL DALAM UPAYA MENINGKATKAN KETUNTASAN BELAJAR FIQIH MATERI WUDHU DAN TATA CARANYA PADA PESERTA DIDIK KELAS I- ARRAHMAN (PIONIR: JURNAL PENDIDIKAN, 2022)
This study examines how to increase students' learning mastery and learning activities on ablution material and procedures through the application of contextual approach in class I-Arrahman MIN 27 Aceh Besar, Semester Genap, 2020/2021 Academic Year. In order to obtain answers to these problems, class action research method through a qualitative approach is used in this study. The subjects of this study were 31 students of class I-Arrahman. The results of the study obtained that the percentage of student learning outcomes in the first cycle is 61.29% with an average student learning outcome is 67.41, the second cycle is 80.64% with an average student learning outcome is 76.29, and the third cycle is 90.32% with an average learning outcome is 82.58, and classical learning is also completed. It is proven that student learning outcomes through the application of contextual approach in Fiqh subject on ablution material and procedures in class I-Arrahman MIN 27 Aceh Besar have increased in every cycle. The average activity level of students in the first cycle is 2.54, in the second cycle is 3.77 and in the third cycle is 4.23, which reached the good category. Thus, the activities of students during the application of the contextual approach in learning Fiqh on ablution materials and procedures in class I-Arrahman MIN 27 Aceh Besar have increased each cycle so that students are more active and learning is more effective.
Keywords: Contextual approach; Learning Mastery; Learning Activity